2017
DOI: 10.1101/170290
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Single-molecule force spectroscopy of protein-membrane interactions

Abstract: Many biological processes rely on protein-membrane interactions in the presence of mechanical forces, yet high resolution methods to quantify such interactions are lacking. Here, we describe a single-molecule force spectroscopy approach to quantify membrane binding of C2 domains in Synaptotagmin-1 (Syt1) and Extended Synaptotagmin-2 (E-Syt2). Syts and E-Syts bind the plasma membrane via multiple C2 domains, bridging the plasma membrane with synaptic vesicles or endoplasmic reticulum to regulate membrane fusion… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

12
61
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(73 citation statements)
references
References 71 publications
(104 reference statements)
12
61
0
Order By: Relevance
“…The increased binding of Syt1 in the presence of Ca 2+ is also expected from previous work , which indicates that Syt1 reorients to insert the hydrophobic residues of the Ca 2+ loop into the membrane. A recent optical tweezers study reported a binding energy of ~12 k B T in the presence of 0.5 m m free Ca 2+ for C2AB binding to an anionic membrane .…”
Section: Discussionsupporting
confidence: 84%
See 2 more Smart Citations
“…The increased binding of Syt1 in the presence of Ca 2+ is also expected from previous work , which indicates that Syt1 reorients to insert the hydrophobic residues of the Ca 2+ loop into the membrane. A recent optical tweezers study reported a binding energy of ~12 k B T in the presence of 0.5 m m free Ca 2+ for C2AB binding to an anionic membrane .…”
Section: Discussionsupporting
confidence: 84%
“…The increased binding of Syt1 in the presence of Ca 2+ is also expected from previous work , which indicates that Syt1 reorients to insert the hydrophobic residues of the Ca 2+ loop into the membrane. A recent optical tweezers study reported a binding energy of ~12 k B T in the presence of 0.5 m m free Ca 2+ for C2AB binding to an anionic membrane . A wide range of dissociation constants, and therefore binding energetics, have been measured by traditional biological assays for soluble C2AB with anionic membranes, with a maximum value of ~25 k B T .…”
Section: Discussionsupporting
confidence: 84%
See 1 more Smart Citation
“…For Syt1-C2AB induced tethers, the median rupture force most likely represents proteinmembrane interactions with a median rupture force in the 50 -200 pN range, strongly dependent on the Ca 2+ (which regulates C2AB-membrane binding) and protein concentration. The binding force of one Syt1 molecule to a membrane is in the range of several pN (43). Therefore, the differences we observe in the force probably relate to a variation in the number of bound molecules.…”
Section: Discussionmentioning
confidence: 75%
“…The shuttle model is consistent with the hydrophilic nature of the two tips of the SMP domain and with the lack of evidence for the property of the SMP domain to form tetramers or longer adducts to bind and bridge the two bilayers 10 properties 18,24 . The C2A domains of the E-Syts bind membranes in a Ca 2+ -dependent way 18,24,43 and were proposed to bind the plasma membrane 44 . However, the length of the unstructured linker that separates it from the SMP domain is too short (~ 8 nm when fully stretched) to span the ER-plasma membrane distance when the SMP domain is in close proximity of the ER during its shuttling.…”
Section: Discussionmentioning
confidence: 99%